Fabrication of an In2O3 NP-based high-performance low-operating voltage phototransistor and tuning of its photosensitivity from UV to blue region - Yadav A.K.; Pandey U.; Aich P.K.; Acharya V.; Suman S.; Pal B.N. (My University, 2025)
In this work, a visible-blind low-operating voltage phototransistor was fabricated using colloidal In2O3 nanoparticles (NPs) via a solution process technique, and its photosensitivity was tuned to the blue region by adding a PbI2 layer to the channel. The low-voltage operation of this thin-film transistor (TFT) was achieved by employing an LiInSnO4 gate dielectric with high areal capacitance, which originated from the mobile Li+ ions inside the dielectric thin film. Furthermore, the photosensitivity of the low-voltage TFT was improved through the implementation of an asymmetric source-drain (S-D) electrode of TFT with different work functions, which worked as a driving voltage for photo-generated carriers. Specifically, LiF/Al and MoO3/Ag were used as source and drain electrodes, respectively, which exhibited a work-function difference of ∼−1.16 eV. Incorporating these asymmetric S-D electrodes markedly improved the performance of the In2O3 NP TFT, reducing the subthreshold swing (SS) from 682 to 160 mV per decade, representing a fourfold decrease, and enhancing the on/off current ratio by an order of magnitude. As the band gap of In2O3 NP was ∼3.7 eV, the device was sensitive only towards deep UV region, making it a visible-blind device. The photosensitivity of the device under UV illumination was enhanced by twenty times using the asymmetric S-D electrodes. The photo-response band of this TFT was further tuned to the blue region by adding a PbI2 layer on the In2O3 channel of the TFT. The photosensitivity of the asymmetric electrode-based PbI2/In2O3 heterojunction TFT in the deep UV (∼395 nm) and blue (∼445 nm) regions was 492 and 152, respectively. © 2025 The Royal Society of Chemistry.